Do manuscrito ao livro impresso I - Maria Cristina Carrington (Outros Títulos, 2019)
This work aims to promote a broad critical reflection on the birth and evolution of writing and of book publishing throughout the ages, highlighting the main supports and techniques, from the scroll of papyrus to the parchment codex, from the book on paper to the digital book. The articles in this volume deal with various themes concerning the History of the Book and the Publishing Industry from antiquity to present-day. They are the culmination of a project which is intended to be continued, thus renewing our attempt to disseminate the Arts of the Book.